Оценка оптимального размера капель огнетушащих гелеобразующих систем - Sharshanov Андрей; Abramov Юрий; Kireev А. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
Mathematical modeling of the behavior of droplets of gel-forming fire extinguishing systems in their flight through combustion area was carried out. For this purpose, the problem of evaporation of a droplet of water saline solution in the hot gas environment was considered. Basing on the model developed, an estimate was made of the minimal initial diameter of droplets ensuring reliable gel formation on the surfaces under treatments. The minimal initial droplet diameter values were obtained as the result of analysis of numerical solutions of equation systems using «Matlab» software. At the droplets movement rates of 10 m/s and 20 m/s, the minimal initial diameters are 1.1 mm and 0.8 mm respectively.